Diversity and abundance of Dacinae fruit flies (Insecta: Diptera: Tephritidae) in Chini 2, Runchang and Sungai Bebar, Pahang, Peninsular Malaysia - Yong, Hoi Sen; Ng, Y.F.; Lim, Phaik Eem (Akademi Sains Malaysia & Confederation of Scientific & Technological Association in Malaysia (COSTAM), 2010)
The diversity and abundance of Dacinae fruit flies of the family Tephritidae were studied at seven localities in the Pekan District, Pahang Darul Makmur, in the east coast of Peninsular Malaysia. Male fruit flies were collected in the morning by using the attractants methyl eugenol and cue-lure. Three species (Bactrocera carambolae, Bactrocera papayae and Bactrocera umbrosa) of the methyl eugenol group were recorded. Bactrocera carambolae was present in all seven localities, being most abundant in a forest fringe locality near a river but uncommon in the two Sungai Bebar localities. Bactrocera papayae was present in four localities with human habitation but absent in the three forest areas. It was most common in the two localities in Chini 2 with village setting. Bactrocera umbrosa was found in three localities with typical village setting with fruit trees of Artocarpus species. The cue-lure group was present in five of the seven localities studied. Four species were present – Bactrocera infesta, Bactrocera melastomatos, Bactrocera nigrotibialis and Bactrocera cf tau. Bactrocera nigrotibialis was the predominant species while B. infesta occurred in quite large number in a river bank locality. The other two species (B. melastomatos and B. cf tau) appeared to be uncommon. Bactrocera infesta represented the first documented record for Peninsular Malaysia.